Teoria da relatividade : uma proposta didática para o ensino médio - Giacomelli, Alisson Cristian (2016)
The present study consists of a dissertation presented to the Postgraduate Program in Teaching Science and Mathematics (PPGECM) of the University of Passo Fundo (UPF), in the line of research - Theoretical-methodological Foundations for the teaching of Sciences and Mathematics. The objective of the work is to structure a didactic proposal for the insertion of topics of the theory of restricted relativity (TRR) and the theory of general relativity (TRG) in high school. The educational product resulting from this work is constituted by a supporting text in which a set of didactic resources in the form of texts, experimental activities, classroom dynamics, etc. is presented. Which cover TRR and TRG topics. The theoretical basis is based on French didactics, more specifically on the theory of didactic transposition in the perspective of Yves Chevallard, added by the discussions of Jean-Pierre Astolfi. As a subsidy for the preparation of the support text, an analysis was made on the TRR and TRG topics that are addressed in the high school textbooks recommended by the National Textbook Program (PNLD) 2015. The application of the educational product occurred in a Graduates in Physics at the University of Passo Fundo (UPF) as a way of evaluating the didactic feasibility of the material. With the results of the research carried out during the application of the educational product, it was possible to verify some aspects regarding the acceptance and assimilation of the group with respect to the presented proposal